A sun-and-beach resort intertwined with a National Park. Disputes over the meaning of Cabo Polonio (Uruguay) in the name of touristic differentiation - de Souza, Gabriel; Dabezies, Juan Martin (Revista de Antropología Social, 2024)
Cabo Polonio is a small coastal village in the southeastern Uruguay of great tourist and environmental interest. In addition to being part of the National System of Protected Areas as a National Park, it is a sun and beach resort emblematic of the Uruguay Natural tourist brand. This polyvalence places us before two intertwined heritage reference frameworks. In this configuration of protected area and beach town, public and private actors dispute the ligitimacy of their practices to guide the meaning of their actions in inhabiting, vacationing, visiting, or managing the uses and benefits of value extraction, sparking controversies about what should be sustained and for whom. Where there was once a village of sea lion hunters and fishermen, today exploitation and conservation practices are intertwined in the name of constructing tourist differentiation, which drives or postpones the degradation of the social and biological environments that sustain it. Paradoxically, tourist practices also propose a journey back in time to recreate a refuge against developmental values and practices.
Keywords: protected areas; tourism; Uruguay; heritagization; conservation